Looking Like a Million Dollars: Does Attractiveness Priming Increase Altruistic Behavior in Experimental Games? - Novakova, Julie; Machová, Kamila; Sýkorová, Katerina; Zíka, Vojtěch; Flegr, Jaroslav (Frontiers in Psychology, 2021)
The emergence of altruistic behavior constitutes one of the most widely studied problems in evolutionary biology and behavioral science. Multiple explanations have been proposed, most importantly including kin selection, reciprocity, and costly signaling in sexual selection. In order to test the latter, this study investigated whether people behave more altruistically when primed by photographs of attractive faces and whether more or less altruistic people differ in the number of sexual and romantic partners. Participants in the general population (N = 158, 84 F, 74 M) first rated the attractiveness of photographs of 20 faces of the opposite (sexually preferred) sex and then played the Dictator and Ultimatum Games (DG and UG). The photograph rating acted as priming; half the participants received photographs of people rated as more attractive than average in an earlier study, and the other half received photographs previously rated as less attractive. The attractiveness-primed participants, especially men, were expected to behave more altruistically—signaling that they are desirable, resource-possessing partners. We also expected altruists to self-report more sexual and romantic partners. The observed difference between altruistic behaviors in the attractiveness- and unattractiveness-primed groups occurred in UG offers, however, in the opposite than expected direction in women. The number of sexual partners was positively correlated to minimum acceptable offers (MAOs) in the UG, in line with expectations based on the theory of costly signaling.